Value-Based Organizational Culture in Islamic Schools: A Comparative Study of Prescriptive and Adaptive Models - Zahida Solusia Khoirunnisa; Aman Aman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2026)
Organizational culture has been widely recognized as a critical factor in educational effectiveness; however, limited research has examined how it functions as a managerial system within Islamic schools. This study aims to analyze the role of organizational culture in educational management and to compare its implementation in two Islamic secondary schools in Yogyakarta, Indonesia: SMA SahabatQu Fullday School and MAN 1 Yogyakarta. A qualitative multiple-case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving principals, vice principals, teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that organizational culture functions not merely as an institutional identity but as a management system that shapes planning, organizing, implementation, and control processes. SMA SahabatQu applies a highly structured cultural approach grounded in Qur’anic values, intensive mentoring, and systematic monitoring, while MAN 1 Yogyakarta adopts a more adaptive approach that integrates Islamic values, local wisdom, and dialogic leadership. The study also reveals that religious and cultural practices contribute to students’ educational experiences by fostering a sense of belonging, social cohesion, and personal development. Based on the cross-case analysis, two conceptual models are proposed: the Prescriptive-Holistic Cultural Model and the Adaptive-Contextual Cultural Model. This study contributes to the literature on Islamic educational management by demonstrating that value-based organizational culture operates through multiple cultural pathways shaped by institutional context, leadership philosophy, and educational goals.